Fear and segregation: anxiety beyond the gated communities. The Costa Rican case - Barrantes Chaves, Karla (AESOP, 2019)
Fear of crime is a constant concern in Latin America. In Costa Rica, those feeling seems to be changing the urbanisation patterns; giving way to gated communities. However, those developments might be increasing feelings of exclusion and anxiety instead of reducing crime. In the last 25 years, the gated communities have been rising; as a result, the traditional neighbourhoods have to coexist with these new developments. This paper aims to explore the effects of gated communities in the distribution of fear in their peripheries, mainly those regarding tensions between outside – inside. The research is taking place within the Greater Metropolitan Area of Costa Rica. Eight open neighbourhoods were selected, using the poverty indicator basic unfulfilled needs (NBI). In each case was carried out a walking interview with some members of the community; those walks were tracked with a GPS and recorded. Additionally, there were focus groups, observations and interviews. Some preliminary results suggest significant residential segregation between the neighbourhoods and the gated communities. It seems the fortification is more than a physical barrier; there is no room for sharing, which causes misconceptions and fears towards other people. Keywords: Fear of crime, gated communities, Costa Rica, residential segregation.
Planning for Transition – book of proceedings 31; 2